Toward a Resource Theory of Fathering. Issue 1 (26th February 2018) - Palkovitz, Rob; Hull, James
Abstract: A resource model of fathering is elaborated as a proposed midrange father‐centered theory that provides a comprehensive framework for integrating the fathering literature. By explaining how fathers manage multiple components of fathering across levels and domains that are embedded within personal, interpersonal, and community contexts, the proposed theoretical model incorporates cognitive, affective, and behavioral aspects of lived experiences. Integrating existing theories to explain observed diversity in common measures of fathering, including assessments of father–child attachment, paternal style, and father involvement, the proposed theory provides direction for advancing an understanding of fathering by identifying under‐researched associations between fathers and the contexts and relationships in which they are embedded with the potential for informing fathering education and intervention.